The design and implementation of Malaysian indigenous herbs knowledge management system based on ontology model - Sahri, Zulazeze; Abd Aziz, Muhd Eizan Shafiq; Ramli, Nazirah; Canda, Roger (2016)
This paper introduces the design and implementation of an Ontology-Based Malaysian Herbal Knowledge Based System (MiHerbs).The ontology model used in this research is based on a previous research with title, ’Malaysia Indigenous Herbs Knowledge Representation’.The research proposed an Ontology based knowledge representation model of Malaysian indigenous herbs using Web Ontology Language (OWL).The model can be used to encode and store knowledge in a “Knowledge Base” such as database, repository or library. The model also can enhance search formulation in information retrieval of herbal knowledge with ease, fast and accurate.However, the back end databases which is based on the OWL language needs to be transformed to relational database format. The transformation from OWL to Relational database is based on the OWL2DB algorithm guideline will be further discussed in this research.Assisted by the System Development Life Cycle (SDLC) methodology, MiHerbs is expected to help herbal research agencies, private sector and government to store and share their herbal related information via the system to provide an ease information access to public or even people around the world.